(untitled) (Research, Society and Development, 2022)
Objectives: To identify the main risk factors related to skin problems related to the use of personal protective equipment (PPE)/vestments and the main preventive measures. Methodology: Quantitative descriptive exploratory research, data collected in January 2022 with professionals working during the coronavirus (COVID-19) pandemic who underwent the use of PPE/garment at a university hospital in Rio de Janeiro. Results: 84 professionals were interviewed, being 56 (66.7%) female and 28 (33.3%) males. The white race (60%) and the age group between 20 and 30 years (44%) prevailed. Nursing professionals were the most affected (50%). Regarding the signs and symptoms reported during the use of PPE, 71 (85%) reported the occurrence of redness in the skin, 30 (36%) pressure on the skin, 55 (65%) change in humidity, 51 (60%) reported pain or burning and 24 (28%) skin changes that may have been secondary to one or more risk factors mentioned above. Conclusion: The pandemic scenario generated additional risk for persistence of risk factors due to the prolonged use of PPE/vestments as it determined their continuous use for long periods and sometimes without respecting safe prevention measures. The maintenance of risk factors (pressure, friction and humidity) was observed during the use of the PPE necessary for protection with a view to maintaining care. Therefore, there is a need for health education of the health team on the main preventive measures that must be carried out in order to avoid changes in the integrity of the skin, which is fundamental for the health of the worker.